(untitled) (Journal of Parents and Teachers, 2025)
The article refers to different love stories, those that do not have a happy ending, or if they do, it’s not with the person everyone expected. In some cases, the romance is long-lasting, while in others, it is accompanied by conflicts and weaknesses that cause the love to erode and resentment to arise, leading to infidelities and separations. Based on the above, a series of causes that generate all of the aforementioned are presented: social, psychological, chemical, and legal causes. Additionally, the role of lawyers and children is discussed, as the latter are the ones who endure all these changes and processes.